The daily co-curricular management practises in a secondary school - Noor Azzam Syah Mohamed; Noor Hassline Mohamed; Amoneeta Beckstein; Noor Azzura Mohamed (Journal of critical reviews, 2020)
This case study is designed to explore the implementation practises of co-curricular management at a secondary school among five teachers who were involved in a co-curricular management group in Selangor, Malaysia. This study was implemented based on Stoner, Freedmen and Gilbert’s management theory and also Gulick’s management principles with minor alterations to fit the study needs. This qualitative study selected participants based on purposive sampling methods in order to facilitate an in-depth understanding of the phenomena in question. Data was obtained from in-depth interviews, direct observation and document analysis. All participants provided their opinions about the co-curricular management implementation and processes at the secondary school. The data collection and analysis process were conducted simultaneously and continuously until data saturation was achieved. The constant comparative method was utilised to analyse the data. Generally, this study’s results showed that there were six aspects of co-curricular management practised by the school’s cocurricular management group in order to maintain co-curricular excellence. These aspects were the planning of co-curricular activities, organising the co-curricular activities, leading the co-curricular activities, controlling the co-curricular activities, conducting staff development training on co-curricular activities, and liaising with the outside community to assist with co-curricular activities in schools.